The Effects of High Intensity Interval Training vs Steady State Training on Aerobic and Anaerobic Capacity - Foster, Carl; Farland, Courtney V; Guidotti, Flavia; Harbin, Michelle; Roberts, Brianna; Schuette, Jeff; Tuuri, Andrew; Doberstein, Scott T; Porcari, John P (Journal of sports science & medicine, 2015)
High intensity interval training (HIIT) has become an increasingly popular form of exercise due to its potentially large effects on exercise capacity and small time requirement. This study compared the effects of two HIIT protocols vs steady-state training on aerobic and anaerobic capacity following 8-weeks of training. Fifty-five untrained college-aged subjects were randomly assigned to three training groups (3x weekly). Steady-state (n = 19) exercised (cycle ergometer) 20 minutes at 90% of ventilatory threshold (VT). Tabata (n = 21) completed eight intervals of 20s at 170% VO2max/10s rest. Meyer (n = 15) completed 13 sets of 30s (20 min) @ 100% PVO2 max/ 60s recovery, average PO = 90% VT. Each subject did 24 training sessions during 8 weeks. There were significant (p < 0.05) increases in VO2max (+19, +18 and +18%) and PPO (+17, +24 and +14%) for each training group, as well as significant increases in peak (+8, + 9 and +5%) & mean (+4, +7 and +6%) power during Wingate testing, but no significant differences between groups. Measures of the enjoyment of the training program indicated that the Tabata protocol was significantly less enjoyable (p < 0.05) than the steady state and Meyer protocols, and that the enjoyment of all protocols declined (p < 0.05) across the duration of the study. The results suggest that although HIIT protocols are time efficient, they are not superior to conventional exercise training in sedentary young adults. Key pointsSteady state training equivalent to HIIT in untrained studentsMild interval training presents very similar physiologic challenge compared to steady state trainingHIIT (particularly very high intensity variants were less enjoyable than steady state or mild interval trainingEnjoyment of training decreases across the course of an 8 week experimental training program.